2008
DOI: 10.1111/j.1745-4549.2008.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Process Parameters for Ready-to-Eat Shrimp Curry in Tin-Free Steel Cans

Abstract: Polymer‐coated tin‐free steel cans were evaluated for their suitability for canning and storage of ready‐to‐eat fish products. The cans were found to withstand the thermal processing conditions and suitable for food contact application. The overlap was 63%, which was well above the prescribed limit of 45%. Blanched shrimps were used for preparing three different styles of shrimp curry from which one was selected based on sensory evaluation. Shrimp curry prepared according to the standard recipe was processed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
1
22
2
Order By: Relevance
“…In the present study, Cg was observed to be 88.79 min indicating better nutrient retention. Cook value observed in the present study is similar to the values reported for mackerel in brine processed at 121.1 °C [32] whereas slightly higher values were reported for prawn kuruma in retortable pouch and aluminium cans [17].…”
Section: Heat Penetration Characteristicssupporting
confidence: 89%
“…In the present study, Cg was observed to be 88.79 min indicating better nutrient retention. Cook value observed in the present study is similar to the values reported for mackerel in brine processed at 121.1 °C [32] whereas slightly higher values were reported for prawn kuruma in retortable pouch and aluminium cans [17].…”
Section: Heat Penetration Characteristicssupporting
confidence: 89%
“…Condensed cream of celery soup was reported to have a j h value of 1.3 (Berry & Bradshaw, 1980). Ready-to-eat shrimp curry exhibited a j h value in the range of 1.12e1.49 for F o 6.0 min to F o 8.0 min, when processed in tin-free steel cans using a rotary retort (Sreenath et al, 2008). Large j h values for agitated processes indicated that product agitation processes did not commence with heating, but only after some time are the viscous forces of the product overcome by the inertial forces induced by the rolling of the can (Berry & Bradshaw, 1980).…”
Section: Resultsmentioning
confidence: 98%
“…Retorting has been for increasing the shelf life for several food products such as seer fish curry (Ravishankar, Gopal, & Vijayan, 2002), tuna in oil (Ali, Sudhir, & Gopal, 2006), tuna in oil and brine , readyto-eat pearl spot fish curry (Pandey, Jayathilakan, Mallika, & Jayakumar, 2007), prawn kurma (Mohan, Ravishankar, Bindu, Geethalakshmi, & Gopal, 2006;Mohan, Ravishankar, Gopal, & Bindu, 2008), mushroom in brine (Chandrashekar, Gopal, & Rai, 2004), mushroom curry (Chandrashekhar, Rai, Gopal, & Verma, 2001), ready-to-eat 'Fish Peera' from Anchovy (Stolephorous commersoni) (Bindu, 2010), seer fish moilee (Manju et al, 2004), mussel meat (Bindu, Gopal, & Nair, 2004). In the recent past, tin-free steel cans have been widely used for thermal processing of shelf stable food products such as ready-to-eat squid masala (Gopinath, Anthony, Ravishankar, Bindu, & Gopal, 2007), ready-to-eat shrimp curry (Sreenath, Abhilash, Ravishankar, & Gopal, 2008) and Indian mackerel in brine (Sreenath, Abhilash, Ravishankar, Anandan, & Gopal, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…The f h for all other products ranged between 16 and 19.3 min. f h value observed in the present study was lower than squid masala (Sreenath et al ., ) and prawn curry in TFS cans (Sreenath et al ., ) and prawn kuruma in aluminium cans (Mohan et al ., ). This could be due to the brine medium used in the present study in which the heating rate will be faster compared with thicker curry, masala and kuruma mediums.…”
Section: Resultsmentioning
confidence: 99%